LANGUAGE STYLE USED BY THE MAIN CHARACTER ROMAN PEARCE IN “FAST & FURIOUS 9” MOVIE - Kelbulan, Beno; Mustikawati, Yunitari; Nurfadhilah, Auliyanti Sahril (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
Different sorts of dialect styles can be watched in little things in life and in numerous expressions. Each diverse environment will have a distinctive dialect fashion. This study discusses about fashion of dialect within the film script entitled Fast and Furious 9. In this study, the researcher points to study the style of dialect utilized by the most character